So you want to write a novel - Stanek, Lou Willett Ph.D
Practical advice, hands-on help. Respected author and professional writing instructor Lou Willett Stanek's New York workshop have enabled scores of aspiring novelist to realize their dreams of completing credible and compelling manuscripts. Here, in a positive, "user-friendly" format, she offers not only encouragement and motivation, but clear step-by-step instructions to accomplish your goal--from original conception through final draft.